Progression of age-related geographic atrophy: role of the fellow eye - Fleckenstein, Monika; Schmitz-Valckenberg, Steffen; Adrion, Christine; Visvalingam, Sivatharisini; Göbel, Arno P.; Mössner, Andreas; Strachwitz, Claudia N. von; Mackensen, Friederike; Pauleikhoff, Daniel; Wolf, Sebastian; Mansmann, Ulrich; Holz, Frank G. (Investigative ophthalmology & visual science, 2011)
To evaluate the role of fellow eye status in determining progression of geographic atrophy (GA) in patients with age-related macular degeneration (AMD). A total of 300 eyes with GA of 193 patients from the prospective, longitudinal, natural history FAM Study were classified into three groups according to the AMD manifestation in the fellow eye at baseline examination: (1) bilateral GA, (2) early/intermediate AMD, and (3) exudative AMD. GA areas were quantified based on fundus autofluorescence images using a semiautomated image-processing method, and progression rates (PR) were estimated using two-level, linear, mixed-effects models. Crude GA-PR in the bilateral GA group (mean, 1.64 mm2/y; 95% CI, 1.478-1.803) was significantly higher than in the fellow eye early/intermediate group (0.74 mm2/y, 0.146-1.342). Although there was a significant difference in baseline GA size (P = 0.0013, t-test), and there was a significant increase in GA-PR by 0.11 mm2/y (0.05-0.17) per 1 disc area (DA; 2.54 mm2), an additional mean change of −0.79 (−1.43 to −0.15) was given to the PR beside the effect of baseline GA size. However, this difference was only significant when GA size was ≥1 DA at baseline with a GA-PR of 1.70 mm2/y (1.54-1.85) in the bilateral and 0.95 mm2/y (0.37-1.54) in the early/intermediate group. There was no significant difference in PR compared with that in the fellow eye exudative group. The results indicate that the AMD manifestation of the fellow eye at baseline serves as an indicator for disease progression in eyes with GA ≥ 1 DA. Predictive characteristics not only contribute to the understanding of pathophysiological mechanisms, but also are useful for the design of future interventional trials in GA patients. (ClinicalTrials.gov number, NCT00393692.)
Veröffentlichung angenommen am 4. Juli 2011
Gesehen am 18.01.2023